Pre-reading: A Guide for Teachers and Parents - Macmillan Reading Scheme (Macmillan Education Limited, 1977)
This book is written for teachers and parents.It is designed to help them in the crucial task of teaching a child to read.
Keywords: Education-Reading Guide